BEBERAPA ASPEK BIOLOGI Telenomus sp. (HYMENOPTERA: SCELIONIDAE) SEBAGAI PARASIT TELUR PENGGEREK KUNING PADI Scirpophaga incertulas (LEPIDOPTERA: PYRALIDAE) - Very Gameriawati; Mohammad Amir (Research Center for Biology-Indonesian Institute of Sciences, 2000)
Various biological aspects o/Telenomus sp.(Hymenoptera: Scelionidae) an eggs parasite of the rice stem borer Scirpophaga incertulas (Lepidoptera: Pyralidae) was conducted in the Pest Laboratory for Crop Institute, Bogor, Indonesia.The results showed that the parasite is solitary in habit and mainly live in eggs of the rice stem borer.The arfu Telenomus could maintain longer life span (3.4 days) in the cage and produced a large number of progenies (29.4 individuals) when they were given food of 10% honey solution compared to those which were given only water (2.1 days of life span, and 22.4 individual progenies).The parasite life span and the number of progenies were the least (1.8 days of life span, and 18.8 individual progenies) when they were treated without any food.The number of progeny was also the greatest when they were provided with one day old of stem borer eggs (45.87 individuals), while the number of progeny declined when they were provided with 2 days (36.93 individual progenies) and 3 days (24.87 individual progenies) old stem borer eggs respectively. Pairs of day old parasites are able to parasite more host eggs compared to that of successive days old parasites.The sex ratimf 2 : 2 produced more progenies compared to that with the sex ratio IS : 2 and 2 : lQ.Parthenogenetic reproduction in arfu Telenomus parasite being tested resulted in the male progenies only.